2017
DOI: 10.1108/ejtd-02-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Military lives: coaching transitions

Abstract: Purpose -The purpose of this study is firstly to consider how veterans employ talk to shape interpretations of personal and social identify. Secondly, we seek to gain an understanding of how veterans see themselves in a civilian world, their ability to re-conceptualise and realign their perspective on life to support their transition in to a civilian world.Design/methodology/approach -Underpinned by Ricoeur's theory of narrative identity, the work provides a qualitative analysis data from coaching interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Essential to transition is the reconstruction of a valued self-identity. Military veterans who remain captives of their past often have difficulty reconciling their civilian and military selves (Beech et al, 2017; Higate, 2001). Servicemen and servicewomen who retire from the military have been shown to encounter very different experiences to people who retire from conventional civilian life and, for many, the transition back into civilian life is replete with difficulties and challenges (Carlson et al, 2013; Herman and Yarwood, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential to transition is the reconstruction of a valued self-identity. Military veterans who remain captives of their past often have difficulty reconciling their civilian and military selves (Beech et al, 2017; Higate, 2001). Servicemen and servicewomen who retire from the military have been shown to encounter very different experiences to people who retire from conventional civilian life and, for many, the transition back into civilian life is replete with difficulties and challenges (Carlson et al, 2013; Herman and Yarwood, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Retirement from the military is a challenging life-transition that can strongly impact on personal identity (Beech et al, 2017) and sense of self, yet the lived, embodied experiences of transition to retirement are under-researched and not well understood (Bulmer and Eichler, 2017; Cooper et al, 2018; Fossey and Hacker Hughes, 2013; Herman and Yarwood, 2014). According to the UK Ministry of Defence (MOD, 2011) definition, any person who has served in the British armed forces for at least one day is classed as a veteran.…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study of UK general veterans reported that current employment was not grounded in the same level of expertise or skill as previous military roles [23]. This was supported by a study of UK infantry that highlighted a perceived difference between military and civilian roles and a feeling that skills were underused in the new workplace [24].…”
Section: Value Of Military Experiencementioning
confidence: 99%
“…A second difference was communication, interpersonal communication at civilian workplaces felt unfocused to veterans [36]. This was supported by UK veterans who felt there were lots of meetings but very little action, and that direct communication was not the norm [20,24]. American nurse academics elaborated upon this, suggesting that direct communication was met with resistance and needed to be tempered to facilitate effective communication [19].…”
Section: Difference Between Military and Civilian Employmentmentioning
confidence: 99%
“…From a Ricoeurian perspective, what we call “identity work” revolves around idem, ipse, and the perceived relationship between them (see also Beech et al, 2017; Mallett and Wapshott, 2012). Identity work can be said to involve a narrative process of expressing, in dialogue with oneself and others, “the ongoing dialectic of selfhood and sameness” (Rasmussen, 1996: 165).…”
Section: A Ricoeurian Perspective On Identity Workmentioning
confidence: 99%